Total synthesis of peloruside A via kinetic lactonization and relay RCM cyclization reactions (and identification of iso-peloruside A) - Hoye, Thomas R. (2010)
A convergent total synthesis of peloruside A (1) is described. The key strategic features are a diastereoselective lactonization to generate a C5-C9 valerolactone from the C(2)-symmetric ketone 4, which comprises C1–C9 of 1, and a relay ring closing metathesis (RRCM) reaction to produce a dehydrovalerolactone 20, which embodies C13–C19. A new isomer of 1, the valerolactone iso-peloruside A (iso-1), was identified.